The relationship between workplace spirituality and innovative work behavior: the mediating role of perceived person-organization fit - Afsar, Bilal (Journal of management, spirituality & religion, 2015)
There has been minimal research on the impact of an employee's workplace spirituality on his/her innovative work behavior (IWB). The current study aims to fill this gap in the literature. In order to understand the psychology of workplace spirituality, this study has longitudinally analyzed the relationship between workplace spirituality and IWB (self and supervisor-based assessments), and impact of perceived person-organization fit (P-O fit) on this relationship. Data were collected from 448 subordinates and 79 supervisors from two knowledge-intensive industries of Thailand. Structural equation modeling was used to analyze the relationships. Results of the study indicate that employee's workplace spirituality is positively related to both self and supervisor ratings of innovative behaviors, and perception of perceived P-O fit acts as a partial mediator between workplace spirituality and IWB at both Time 1 and Time 2. These results imply that an employee's experience of workplace spirituality impacts his/her perceived P-O fit which in turn helps in engaging him/her to display IWB more often. Study findings begin to explain how workplace spirituality impacts IWB of individuals. Specifically, we find that perceived P-O fit explains the relationship between workplace spirituality and IWB.